Breast Cancer in the Balinese Elderly Population: Analysis of the Hospital-Based Cancer Registry - I Gusti Putu Suka Aryana; Putu A.T Adiputra; Yulan Permatasari; Pande K. A. Prayudi; Hendra P. Setiawan (Indonesian Journal of Cancer, 2022)
Background: The elderly population in Indonesia will continue to increase over the next few decades. Breast cancer is 22.9% of all female cancers, and aging is one of the biggest risk factors. The challenge in managing older cancer patients is the ability to accurately assess whether the expected benefits of treatment outweigh the risks. Epidemiological data is very important for research and the advancement of medical science in the future. Currently, the incidence of breast cancer in Indonesia is 26 per 100,000 population, but the incidence of breast cancer in the elderly is unknown.Methods: This is a descriptive study of all breast cancer cases recorded in the cancer registry of Sanglah General Hospital, the largest cancer registry in Bali. Statistical analyses were conducted using descriptive statistics with the Statistical Package for the Social Sciences version 16.0 (SPSS).Results: From 1997 until 2013, 1,020 cases of breast cancer among Balinese women of various ages were recorded, of which only 78 cases (7.6%) were attributed to the elderly (age ≥ 65 years). At the time of diagnosis, distant metastasis was recorded for 28.9% of the elderly, compared with 24.4% for the younger group of patients (age < 65 years). Locally advanced breast cancer (LABC) was also recorded higher in the elderly (49.4% vs. 47.5%). A lower proportion of primary surgical treatment was recorded for the elderly than for the younger group of patients (69.7% vs. 76.2%). A lower proportion of adjuvant therapy, either by chemotherapy or radiotherapy, was also recorded for the elderly (45.5% vs. 53.4% and 2.6% vs. 4.9%, respectively), but the proportion of adjuvant hormonal therapy was recorded higher in the elderly (1.3% vs. 0.7%). In contrast, palliative care was recorded higher in the elderly (7.7% vs. 5.7%). Unfortunately, no data about survival were available.Conclusions: There is a tendency for older women in Bali to have more advanced disease at the time of diagnosis and receive less surgical treatment as the primary therapy, but they are more likely to receive adjuvant hormonal therapy and palliative care than their younger counterparts. This information should be of major interest to clinicians.